Intervention Module to Train Speech and Language Skills for Children from Birth to Six Years - Swapna N; Jayaram M; Prema KS Rao; Geetha YV; Manjula PV (Journal of All India Institute of Speech and Hearing, 1970)
The present study aimed at developing an intervention module to train speech and language skills in children between birth to six years. The intervention module comprised of a checklist to assess speech and language skills and activities to enhance the same. The checklist was prepared and nalized by establishing various measures of validity and reliability. This was then administered to 365 typically developing children in the age group of birth to six years for standardizing the same. This checklist was also administered on children with hearing impairment and intellectual de cit. Activities were prepared for each item in the checklist. Following the baseline assessment, speci c items and activities were provided to the parents/caregivers to train at home with speci c instructions on regularand systematic documentation of responses. They were followed up periodically. The post training scores were compared with the pre trainingscores which revealed statistically signi cant improvement in the scores in both the groups of children. It can be concluded from the study that the checklist was useful in identifying the baseline levels and the activities in the module were eective in training the children with hearing impairment and intellectual de cit. Future investigations can include the validation of the module on children with other communication disorders.